The effects of acute and prolonged CRAM supplementation on reaction time and subjective measures of focus and alertness in healthy college students - Olson Mark; Hoffman Mattan W; Beller Noah A; Gonzalez Adam; Ratamess Nicholas A; Hoffman Jay R; Purpura Martin; Jäger Ralf (Taylor & Francis Group, 2010)
Abstract Background The purpose of this study was to examine the effect of acute and prolonged (4-weeks) ingestion of a supplement designed to improve reaction time and subjective measures of alertness, energy, fatigue, and focus compared to placebo. Methods Nineteen physically-active subjects (17 men and 2 women) were randomly assigned to a group that either consumed a supplement (21.1 ± 0.6 years; body mass: 80.6 ± 9.4 kg) or placebo (21.3 ± 0.8 years; body mass: 83.4 ± 18.5 kg). During the initial testing session (T1), subjects were provided 1.5 g of the supplement (CRAM; α-glycerophosphocholine, choline bitartrate, phosphatidylserine, vitamins B3, B6, and B12, folic acid, L-tyrosine, anhydrous caffeine, acetyl-L-carnitine, and naringin) or a placebo (PL), and rested quietly for 10-minutes before completing a questionnaire on subjective feelings of energy, fatigue, alertness and focus (PRE). Subjects then performed a 4-minute quickness and reaction test followed by a 10-min bout of exhaustive exercise. The questionnaire and reaction testing sequence was then repeated (POST). Subjects reported back to the lab (T2) following 4-weeks of supplementation and repeated the testing sequence. Results Reaction time significantly declined (p = 0.050) between PRE and POST at T1 in subjects consuming PL, while subjects under CRAM supplementation were able to maintain (p = 0.114) their performance. Significant performance declines were seen in both groups from PRE to POST at T2. Elevations in fatigue were seen for CRAM at both T1 and T2 (p = 0.001 and p = 0.000, respectively), but only at T2 for PL (p = 0.029). Subjects in CRAM maintained focus between PRE and POST during both T1 and T2 trials (p = 0.152 and p = 0.082, respectively), whereas significant declines in focus were observed between PRE and POST in PL at both trials (p = 0.037 and p = 0.014, respectively). No difference in alertness was seen at T1 between PRE and POST for CRAM (p = 0.083), but a significant decline was recorded at T2 (p = 0.005). Alertness was significantly lower at POST at both T1 and T2 for PL (p = 0.040 and p = 0.33, respectively). No differences in any of these subjective measures were seen between the groups at any time point. Conclusion Results indicate that acute ingestion of CRAM can maintain reaction time, and subjective feelings of focus and alertness to both visual and auditory stimuli in healthy college students following exhaustive exercise. However, some habituation may occur following 4-weeks of supplementation.